Mamulengo e brincantes: diversão, arte e cultura - Schneider, Cynthia Campelo (2020)
The research looked into the mamulengo fun and some of its participants in the State of Pernambuco, taking into consideration the creativity, the dialogues between reality and artistic production, enhancing musical art as the main objective of study. To complete this study a bibliographic revision was made visiting the cities of Atlanta, GA, USA, Recife, Lagoa de Itaenga, Glória do Goitá, as well as interviews with masters of mamulengo and the transcription of guidelines of songs created for fun translating the soul of the puppet. .Authors like Luís da Câmara Cascudo, Néstor Garcia Canclini, Michel de Certeau Certeau, Aaron Copland and Cecília Almeida Salles endorsed the thoughts of the research its main object being to investigate how the masters and mamulengueiros create or even recreate the musical participation in this fun. For some, the word mamulengo refers to suttle or soft hands, that is the necessary ability to give live moments to the puppets. Built with mulungu wood, the puppets "come alive" at the moment of the performances, for people of all ages. It is an art that requires from its performer different abilities highlighting improvisation, so that there is no repeated fun even if the same puppets are used. With joyous songs and much good humour, the master of the fun needs much expertise to develop conversations, conduct the fun from inside a tent and sing loudly the old fashion songs as old as the fun itself. In the universe of myths and legends the spot where the fun takes place is called São Saruê, a land that allows for all variety of magic and feelings. Between conflicts and conquests the mamulengo fun follows its course surviving the most varied scourges, launching new performers and the music as one of its main components, because " it is the music that beckons the spirits of the puppets" and makes them come alive.